ANALYSIS OF SOCIAL WELFARE SERVICES FOR STREET CHILDREN - Bermara Giri Menur Sari; Meriyanto; Antonia Junianty Laratmase (Adisam Publisher, 2025)
This research aims to analyze the social welfare services provided to street children, with a focus on basic needs such as education, health, social protection and economic empowerment. Data was collected through literature review. The results of the analysis show that existing social welfare services are still not comprehensive and not well coordinated among various stakeholders such as the government, NGOs, and health and education institutions. In addition, social stigma towards street children is a significant obstacle to the effectiveness of existing programs. To overcome this problem, it is recommended to strengthen multi-stakeholder collaboration networks, increase capacity and service infrastructure, as well as develop programs based on data from monitoring and evaluation results. With a comprehensive and sustainable approach, it is hoped that social welfare services can be more effective in improving the quality of life of street children and increasing their opportunities for a better future.